DANA PIHAK KETIGA, RISIKO KREDIT DAN TINGKAT EFISIENSI OPERASIONAL PADA BANK BUMN YANG TERDAFTAR DI BEI - Evada Dewata; Pramita Wulandari Pasiak (JURNAL RISET TERAPAN AKUNTANSI, 2020)
Banking financial performance shows how well the quality of operational activities has been running well and can compete with other banking financial institutions. This study aims to determine the effect of variable Third Party Funds and Credit Risk on Banking Financial Performance. The sample of this study is the banks of State-Owned Enterprises (SOEs) listed on the Indonesia Stock Exchange in 2008-2017. Third-Party Funds are proxied with total Third Party Funds and Credit Risk is proxied with Non-Performing Loans (NPLs), while the Bank's financial performance is proxied by Operational Income Operating Costs (BOPO). The research sampling technique used a saturated sampling of 40 sample units. The method of multiple linear regression analysis shows the results of the study that simultaneous size variables in the form of DPK and NPL affect the Financial Performance of Banking. Partially, the variables of Third Party Funds and Credit Risk have a significant positive effect on the Bank's Financial Performance. The predictive ability of the two variables on Banking Financial Performance is shown by adjusted R square of 0,622.